Music therapy in UK palliative and end-of-life care: a service evaluation. Issue 3 (22nd February 2018) - Graham-Wisener, Lisa; Watts, Grace; Kirkwood, Jenny; Harrison, Craig; McEwan, Joan; Porter, Sam; Reid, Joanne; McConnell, Tracey Helena
Abstract : Music therapy aligns to the holistic approach to palliative and end-of-life care (PEOLC), with an emergent evidence base reporting positive effect on a range of health-related outcomes for both patient and family carer alongside high client demand. However, the current service provision and the role of music therapists in supporting individuals receiving PEOLC in the UK is currently unknown. Objectives: This service evaluation aims to identify the provision, role and perceived impact of UK music therapists in supporting patients receiving PEOLC, their families and health and social care professionals. Methods: A survey was distributed to the British Association for Music Therapy (BAMT) member mailing list in July 2017. BAMT is the professional body for Health and Care Professions Council registered music therapists in the UK. Results: Fifty respondents identified themselves as music therapists currently working with clients receiving PEOLC. The respondents largely reported (84.7%) less than 10 years of experience working in PEOLC settings, with only a minority receiving statutory funding for their role. Music therapists most commonly reported supporting adults with neurological conditions, cancers and dementia. Conclusions: Although promising that evidence suggests provision of music therapy in UK PEOLC settings in the past 10 years to have increased, lack of sustainable funding suggests the role to not be consistently accessible in PEOLC.